The karate kid (2010) [videorecording (DVD)] - Zwart, Harald, 1965-; Cheng, Long, 1954-; Smith, Jaden, 1998-; Henson, Taraji P. (Sony Pictures Home Entertainment, 2010)
Dre Parker finds himself in China after his mother's latest career move. He and classmate Mei Ying immediately fall for each other, but cultural differences make this friendship impossible. Even worse, his feelings make an enemy of class bully, Cheng who is quite adept at kung fu. Dre turns to maintenance man Mr. Han, who is secretly a kung fu master and learns that kung fu is not about punches and parries, but maturity and calm. However, Dre realizes that this may be the fight of his life.